Pengaruh Perceived Usefulness dan Perceived Ease of Use terhadap Behavioral Intention pada KRS Online - Tri Asih Nur Fatimah; Alifya Puja Anggraeni; Adinda Yulia Prastiwi; Yuwanda Rizqi Rahma; Fatehah Amelia Putri; Joko Tri Nugraha (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
This study aims to empirically analyze the influence of Perceived Usefulness and Perceived Ease of Use on the Behavioral Intention to use the online Study Plan System (SIPADU) among FISIPOL students, class of 2025, at Universitas Tidar. This research is driven by the importance of evaluating academic information systems to ensure they support student productivity effectively. The analytical model is based on the Technology Acceptance Model (TAM), utilizing a quantitative approach with an associative survey method. The population consisted of 750 students, from which a sample size of 89 was initially determined using the Slovin formula with a 10% margin of error. To enhance validity, the target was rounded to 90, ultimately gathering data from 117 respondents through online questionnaires using simple random sampling. Data were collected via Google Forms using a 5-point Likert scale and processed using SPSS. Instrument quality was ensured through validity (Product Moment) and reliability (Cronbach Alpha) tests. Data analysis techniques included multiple linear regression, t-tests for partial effects, F-tests for simultaneous effects, and the coefficient of determination (R²). The results demonstrate that Perceived Ease of Use significantly and positively impacts Perceived Usefulness. Furthermore, both Perceived Usefulness and Perceived Ease of Use exert a positive and significant influence on Behavioral Intention, both partially and simultaneously. Perceived Usefulness emerged as the most dominant factor influencing students' intention to use the system. These findings suggest that to increase student engagement with SIPADU, the university should focus on enhancing system efficiency and user-friendly interfaces to provide clear functional benefits for its users.